(untitled) (Editora Impacto Científico, 2024)
The study analyzed the motivational factors that led individuals to practice ballroom dancing during and after the COVID-19 pandemic. The quantitative and descriptive research was conducted in August 2022 with eight participants, aged 18 and over, from different cities, including Penápolis, Birigui, Lins, and Londrina. Data were collected using the Sports Activity Motivation Questionnaire (QMAD), adapted by Serpa and Frias (1990), and administered remotely. The results showed that the main factor for participation, among both men and women, was "Technical Competence," related to the desire to learn or improve dance skills. Among men, the category "Pleasure/Occupation" also stood out, revealing the use of the practice as a form of leisure and occupation of free time. Among women, in addition to the appreciation of technical competence, the motivation to compete and the search for new friendships were highly relevant, probably associated with the social isolation imposed by the pandemic. Interestingly, factors such as "Physical Fitness" and "Status" were of low importance for both genders. In general, it was found that ballroom dancing was seen as an opportunity not only for technical improvement, but also for socialization, leisure, and coping with the emotional consequences of isolation. It can be concluded that, in the post-pandemic context, ballroom dancing has established itself as an important resource for the resumption of social interactions and the promotion of well-being.